Plus-InVEST Study of the Chengdu-Chongqing Urban Agglomeration’s Land-Use Change and Carbon Storage - Chaoyue Wang; Tingzhen Li; Xianhua Guo; Lilin Xia; Chendong Lu; Chunbo Wang (Land, 2022)
Based on China’s “carbon neutrality” strategy, this study explores the relationship between land-use/cover change and temporal and spatial changes of ecosystem carbon storage in urban agglomerations. Using the Plus-InVEST model, the projected spatial patterns of land use in the Chengdu-Chongqing urban agglomeration in 2030 under natural development and ecological protection scenarios were simulated and predicted, and the characteristics of carbon storage, together with its spatio-temporal dynamics, were evaluated under two scenarios. Results show that: (1) From 2000 to 2020, forests, water areas, construction areas, and unused land continued to increase, while the area of cropland and grassland decreased continuously. During the last 20 years, carbon storage in urban agglomeration showed an increasing trend, with an overall increase of 24.490 × 106 t. (2) Compared with the natural development scenario, forest land, grassland, and water area in 2030 under the ecological protection scenario exhibits a substantial change; the area of construction land is limited; and an ecological spatial effect is reflected. (3) Compared to 2020, carbon storage under natural development and ecological protection scenarios decreased by 50.001 × 106 t and 49.753 × 106 t in 2030, respectively. The stability of carbon storage under the ecological conservation scenario was significantly higher than that under the natural development scenario. Therefore, under the ecological protection scenario, as a result of the coordinated land use of Chengdu-Chongqing, the functions of various regions can be coordinated and carbon storage losses can be mitigated.